Upaya Guru dalam Meningkatkan Kemampuan Berbahasa Arab Siswa di Kelas V MI Syaikh Zainuddin NW Anjani Kecamatan Suralaga - Muh Zulkifli (Al-mujahidah, 2020)
Learning is an activity or a process to acquire knowledge, improve skills, improve behavior, attitudes, and strengthen personality. In the context of becoming to know or the process of acquiring knowledge. The learning process is essentially to develop the activities and creativity of students, through various interactions and learning experiences. However, in its implementation we often do not realize that there are still many learning activities being carried out which actually hinder the activities and creativity of students. Learning Arabic means learning aspects of the language itself, and each aspect of the habit has its own characteristics that differ from one another. In addition, the language learning system planning is prepared based on basic assumptions and principles that must be held and a clear operational rationale and capability. The assumptions and basic principles of learning Arabic are related to the true nature of Arabic learning. Arabic is a language that must be studied, liked, known and can be mastered by generations of Islam which of course goes through long and varied processes either obtained from formal or non-formal processes. The method used in this research is a qualitative research method. qualitative is a deep understanding and interpretation of the meaning, reality and relevant facts. The research results obtained by the researchers were very influential in the teacher's efforts to improve Arabic language skills by using interesting methods by the researchers. After conducting the research, the researchers obtained the efforts made by the teacher to improve the Arabic language skills of class V students of MI Syaikh Zainuddin NW Anjani, namely, explaining the subject matter, providing insight and motivation, giving mufrodats, training them to read in Arabic, using methods appropriate to their circumstances